DAMPAK KEBIJAKAN RESTRUKTURISASI KREDIT USAHA RAKYAT TERHADAP PENERIMAAN KREDIT PADA PT. BANK NEGARA INDONESIA (PERSERO) CABANG SUMBAWA - Nadila Oktavia; Wahyu Haryadi; Nining Sudiyarti (Pusat Riset dan Publikasi, 2023)
This study aims to determine difference of credit receipts before and after the credit restructuring policy on public business credit (KUR) at PT. Bank Negara Indonesia (Persero) Sumbawa Branch. The type of this study was comparative study. The type of data used is quantitative data in the form of credit receipt data at PT. Bank Negara Indonesia (Persero) Sumbawa Branch before and after the implementation of the public business credit (KUR) restructuring policy obtained from documents or archives of reports on the amount of credit receipts for the period March 2020 – October 2021 which have been collected by PT. Bank Negara Indonesia (Persero) Sumbawa Branch. The data analysis technique was carried out using the two average difference test technique which was used to test whether there was a difference in the averages of the two samples tested. This testing technique includes data normality test and paired samples t-test. The results of study showed that there is no significant difference in the level of credit receipts before and after the credit restructuring policy on public business credit (KUR) at PT. Bank Negara Indonesia (Persero) Sumbawa Branch. Even though there has been an increase in credit receipts after the credit restructuring policy on public business credit (KUR) at PT. Bank Negara Indonesia (Persero) Sumbawa Branch, however the nominal increase was so small that it did not have a significant impact on credit receipts at PT. Bank Negara Indonesia (Persero) Sumbawa Branch.